UV SPECTROPHOTOMETRY APPLICATION FOR QUANTITATIVE DETERMINATION OF VINPOCETINE IN DRUG FORMULATIONS - J. V. Monaykina; N. O. Nagorna; V. V. Nagorniy; S. O. Vasjuk (Zaporozhye State Medical University, 2014)
Introduction. In this paper simple, rapid and sensitive assay methods for quantitative determination of vinpocetine in two new drug formulations (suppositories and nasal cream) are proposed. Analysis has been performed directly by using zero-order UV spectrophotometry. It is known from the special literature that the chromatographic techniques used for vinpocetine assay require expensive equipment and are rather time consuming. Therefore UV spectrophotometry is preferable due to its accuracy and simplicity. The object of this study was to develop new, simple, rapid, precise and accurate UV spectrophotometric procedure for the quantitative determination of vinpocetine in suppositories and nasal cream and evaluation of some validation characteristics of the methods. Materials and methods. The objects of the study were the new drug formulations of vinpocetine, namely 0,01 suppositories and 0,5% nasal cream developed by the scientists of The Chair of Technology of Drugs of Zaporizhzhia State Medical University. Distilled water and 0.05M HCl were used as the solvents, working standard sample of vinpocetine was used as a reference standard. Analytical equipment: spectrophotometer Specord 200, electronic balance ABT-120-5DM, measuring glassware of class A. Assay procedure: An accurately weighed sample of cream (1,200 - 2,000 g) or one suppository was dissolved in 0.05M HCl and filtered into a 50,00 ml volumetric flask. Then the solution was brought to the mark with the same solvent and stirred. 3,00 ml or 4,00 ml of the resulting solutions (for suppositories or cream respectively) were transferred into a 25,00 ml volumetric flask and brought to the mark with distilled water. Absorbance was measured at a wavelength of 272 nm on the blank of distilled water. The parallel measurement with 1,00 ml of 0,064% vinpocetine standard solution was carried out. The content of active substance was calculated according to standard formulas. Results. The suggested procedure was successfully applied for the analysis of two new pharmaceutical formulations. The results obtained by applying the proposed procedure were statistically analyzed. Validation studies of the methods confirmed their proper precision and recovery (for cream: 99,73%, RSD% = 0.924, n = 9; for suppositories: 100,3, RSD% = 0,378, n = 9), linearity (for cream: r =0,9999, n=6; for suppositories: r =0,9998, n=6) The received parameters enable the use of developed methods in quantitative pharmaceutical analysis. Conclusions. The applicability of the new procedure is well established by vinpocetine assay in the new drug formulations, namely 0,01 suppositories and 0,5% nasal cream. The developed UV spectrophotometric methods are potentially useful because of their simplicity, rapidity and accuracy. The methods are valid according to the validation requirements of Ukrainian Pharmacopeia.